Pelatihan Pengembangan Pembelajaran ISMUBA Berbasis Teknologi di SMP Universitas Muhammadiyah Makassar - Ferdinan; Mawardi Pewangi; Alamsyah; Nurul Afifah (Jurnal Pengabdian Kampus, 2023)
Teachers are expected to actively engage in developing learning through the utilization of innovative instructional technologies. One of the learning applications that ISMUBA teachers can utilize in their teaching activities is the Nearpod application. The purpose of this engagement is to enhance the teachers' knowledge in becoming familiar with and proficiently using one of the instructional technology applications. The partnering institution in this training activity is SMP Unismuh Makassar. The training subjects are 25 teachers from ISMUBA SMP Unismuh Makassar. The methodology employed in this engagement includes preparation, needs analysis, training module development, module validation, technical preparation, and training implementation. The instrument used is a multiple-choice questionnaire to assess the level of knowledge of ISMUBA teachers from SMP Unismuh Makassar in recognizing various instructional technologies and their utilization. The technique used involves a pretest and post-test, resulting in a highly significant increase in the knowledge of ISMUBA teachers from Unismuh Makassar in utilizing instructional technology, with an achievement rate of 78%, categorized as 'good'.